Coordination of Variables of Nonautonomous Pneumatic Drive with Hydraulic Properties of Supply System - Pavlovich Kuznetsov, Yuri; Anatolevich Zakharov, Lev; Alekseevich Mironov, Anatolii; Leonidovich Khimich, Vladimir; Nikolaevich Khrunkov, Sergey (International Journal of Engineering and Technology, 2018)
This article discusses the issues of operability of nonautonomous pneumatic drive under workshop conditions. It is mentioned that in order to provide efficient operation and achievement of rated modes by nonautonomous pneumatic drive, it is required to coordinate its variables with variables of air supply system. On the basis of one-dimensional equation of adiabatic gas frictional flow in cylindrical pipe, the problem of determination of maximum achievable power by nonautonomous pneumatic drive at fixed hydraulic properties of supply system has been solved. The obtained dependences make it possible to calculate minimum allowed pipeline diameter of supply system providing preset maximum power of pneumatic drive. It is proved that the coefficient of total pressure conservation corresponding to maximum drive power is precisely determined by available pressure drop and does not depend on hydraulic properties of the system, and in order to achieve maximum drive power, strictly determined portion of available flow energy should be consumed for overcoming of the system hydraulic resistance not depending of reduced pipeline length.Â